A Rare Root Canal Configuration of a Maxillary Second Molar with Fused C-shaped Buccal Root and Five Canals: A Case Report and Review of literature - Liu, Dan; Qiu, Lihong; Yu, Jingtao (Iranian Endodontic Journal, 2019)
Having a thorough knowledge of root canal configuration is essential for a successful endodontic treatment. Clinicians should always pay attention to the unusual canal configuration so as to avoid missing extra canals. This paper describes a non-surgical retreatment of a maxillary second molar with two missing root canals; diagnosed by cone-beam computed tomographic (CBCT) imaging. The tooth had three roots and five canals: a C-shaped buccal root fused by mesiobuccal (MB) and distobuccal (DB) roots with three canals (CBCT scanning showed that the second MB canal was closer to the palatal than the buccal side), a mesiopalatal root with one canal, and a distopalatal root with one canal. The purpose of this case report is to remind clinicians of the importance of anatomical variations, and thus, detection of extra canals. Keywords: Maxillary Second Molar; C-shaped Canal; Cone-Beam Computed Tomography